2020
DOI: 10.1016/s2215-0366(19)30414-6
|View full text |Cite|
|
Sign up to set email alerts
|

Disparities in cancer screening in people with mental illness across the world versus the general population: prevalence and comparative meta-analysis including 4 717 839 people

Abstract: Background. Since people with mental illness more likely die from cancer, we assessed whether people with mental illness undergo less cancer screening versus the general population. Methods. Systematic review and meta-analysis of observational studies. Primary outcome was Odds Ratio (OR) of cancer screening in people with mental illness versus the general population. Secondary outcome was prevalence of cancer screening in mental illness. Sensitivity and subgroup analyses considered specific mental illness, dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 92 publications
8
137
1
Order By: Relevance
“…A very large and recent metanalysis involving almost 5 million people (501 559 patients with mental illness, and 4 216 280 controls) from 47 publications and involving many possible mental illnesses (ie, schizophrenia or schizoaffective or psychosis, depression or bipolar disorder or mania, eating disorder or anorexia nervosa or bulimia nervosa or binge eating disorder, obsessive‐compulsive disorders, post‐trauamtic stress disorder, anxiety disorder or panic disorder) provided a global overview of the problem. Data included studies relative to screening for cancer with results showing that screening was significantly less frequent in people with any mental disease compared with the general population for breast cancer, cervical cancer, and prostate cancer, but not for colorectal cancer 26 …”
Section: Prevention Issues and Screening For Cancer In People With Smimentioning
confidence: 99%
“…A very large and recent metanalysis involving almost 5 million people (501 559 patients with mental illness, and 4 216 280 controls) from 47 publications and involving many possible mental illnesses (ie, schizophrenia or schizoaffective or psychosis, depression or bipolar disorder or mania, eating disorder or anorexia nervosa or bulimia nervosa or binge eating disorder, obsessive‐compulsive disorders, post‐trauamtic stress disorder, anxiety disorder or panic disorder) provided a global overview of the problem. Data included studies relative to screening for cancer with results showing that screening was significantly less frequent in people with any mental disease compared with the general population for breast cancer, cervical cancer, and prostate cancer, but not for colorectal cancer 26 …”
Section: Prevention Issues and Screening For Cancer In People With Smimentioning
confidence: 99%
“…Underreporting is more likely for those whose histology or cytology verification is missing, which most commonly occurs when cancer is diagnosed at an advanced stage and the patient receives only palliative care (Barlow et al, 2009). People with schizophrenia have low rates of participation in general health and cancer screening programmes (Fujiwara et al, 2017;Hwong et al, 2020;Solmi et al, 2020), and delayed and late-stage cancer diagnoses are common in this patient population (Farasatpour et al, 2013). To compensate the underreporting in the Swedish Cancer Register and minimise possible differential completeness in reporting, we used additional data on incident cancers from other nationwide registers, including the National Patient Register or the Swedish Cause of Death Register.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Lindamer and colleagues [77] found that women with schizophrenia took part in pelvic examinations, Pap tests and mammography screening significantly less frequently than controls [77]. This relatively low participation in cancer screening is also true for breast and colon screening [78,79].…”
Section: Treatment and Health Care Needs In Women With Schizophrenia mentioning
confidence: 99%